2015
DOI: 10.1039/c5cp02613j
|View full text |Cite
|
Sign up to set email alerts
|

Illuminating CO2 reduction on frustrated Lewis pair surfaces: investigating the role of surface hydroxides and oxygen vacancies on nanocrystalline In2O3−x(OH)y

Abstract: Designing catalytic nanostructures that can thermochemically or photochemically convert gaseous carbon dioxide into carbon based fuels is a significant challenge which requires a keen understanding of the chemistry of reactants, intermediates and products on surfaces. In this context, it has recently been reported that the reverse water gas shift reaction (RWGS), whereby carbon dioxide is reduced to carbon monoxide and water, CO2 + H2 → CO + H2O, can be catalysed by hydroxylated indium oxide nanocrystals, deno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

17
220
2
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 215 publications
(243 citation statements)
references
References 44 publications
17
220
2
4
Order By: Relevance
“…We attribute this effect to a decrease in the number of active defect sites, specifically surface hydroxides and oxygen vacancies, within the material (18). In a separate study, which combined theoretical simulations and kinetics experiments, we have confirmed that both hydroxides and oxygen vacancies are needed at the active site to facilitate the reduction of CO 2 to CO (17). Significantly, we were able to demonstrate that there is a 20-kJ/mol reduction in the apparent activation energy for the lightdriven reaction relative to the dark reaction, indicating that light plays an important role in activating this defected In 2 O 3-x (OH) y material to facilitate photocatalysis on its surface.…”
Section: Resultsmentioning
confidence: 52%
See 3 more Smart Citations
“…We attribute this effect to a decrease in the number of active defect sites, specifically surface hydroxides and oxygen vacancies, within the material (18). In a separate study, which combined theoretical simulations and kinetics experiments, we have confirmed that both hydroxides and oxygen vacancies are needed at the active site to facilitate the reduction of CO 2 to CO (17). Significantly, we were able to demonstrate that there is a 20-kJ/mol reduction in the apparent activation energy for the lightdriven reaction relative to the dark reaction, indicating that light plays an important role in activating this defected In 2 O 3-x (OH) y material to facilitate photocatalysis on its surface.…”
Section: Resultsmentioning
confidence: 52%
“…4B). Our previous work with these materials has shown that CO 2 binds weakly to the surface of defected indium oxide, generally as carbonate, bicarbonate, and formate species (17,18). These weakly adsorbed species could impact the relaxation dynamics by altering the energetics of the surface.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sample Bi‐0.5%, however, showed a markedly decreased CO production rate (Table S2, Supporting Information). The presence of fewer hydroxide groups and oxygen vacancy surface defects should have resulted in lower photocatalytic activity, due to a reduced number of active sites 26, 33. However, as shown in the XPS and CO production rate results, the CO production rate increases in accordance with a volcano‐shaped trend despite the decreasing number of defects between Bi‐0% and Bi‐0.1% (Figure 4b).…”
Section: Resultsmentioning
confidence: 93%